Effects of hydrophilic and hydrophobic nanosilica on the hydromechanical behaviors of mudstone soil. (9th May 2022) - Ghadr, Soheil; Liu, Chih-Hsuan; Mrudunayani, Pattela; Hung, Ching
Highlights: NS treatment can improve the compressive strength of mudstone soils. The mudstone soils treated with 0.3% NS, regardless of type, lead to the highest UCS. NS-HPI may be a better treatment than NS-HPO to strengthen mudstone soils. The hydromechanical behavior of mudstone soils can be improved by NS treatment. Abstract: In this study, the effects of hydrophilic (HPI) and hydrophobic (HPO) nanosilicas (NS) on the hydromechanical properties of mudstone soil were investigated in a laboratory. Mudstone soil samples treated with different contents (0.3%, 0.6%, 0.9%, and 1.2%) of both types of NS were prepared and rigorously examined through standard Proctor compaction, unconfined compression, three-dimensional volumetric shrinkage, and one-dimensional consolidation tests. In addition to the hydromechanical tests, nondestructive tests, including X-ray diffraction, X-ray fluorescence, and Fourier-transform infrared spectroscopy, were employed to inspect the geochemical and mineral composition of treated and untreated samples. Finally, scanning electron microscopy was used to monitor the packing state of the specimens. The experimental results reveal that the shrinkage and compressibility characteristics of mudstone soils can be significantly improved through NS treatment. In particular, the results demonstrate that the mudstone soils treated with 0.3% NS, regardless of type, had the highest compressive strength. Our results provide insight into the contribution of NS to the hydromechanical properties of mudstone soils and suggest that NS-HPI may be a better treatment than NS-HPO due to its improved ability to strengthen mudstone soils.